THE EFFECT OF RUNNING DICTATION METHOD ON STUDENTS’ WRITING ABILITY In PROCEDURE TEXT (A STUDYATTHE XITH GRADE STUDENTS OF SMA NEGERI 6 PADANGSIDIMPUAN) - Desy Yolanda (JURNAL LINER (Language Intelligence and Educational Research), 2019)
The objective of this research is to know whether there is a significant effect of Running Dictation Method on Students’ Writing ability in procedure text at the eleventh grade students of SMA Negeri 6 Padangsidimpuan. This research uses experimental method with research one group pre-test post-test design. The population of this research is all of eleventh grade students of SMA Negeri 6 Padangsidimpuan which consist of one class. The total population are 31 students. Technique that used on this research is systematic sampling. That consist of 302 students and systematic sampling 31 students. The technique for collecting data by observation sheet and giving test. . The result mean of the application of Running Dictation Method was 3.3, it was categorized ”Good”. The result show score before using Running Dictation Method was 68,54, it was categorized “Fair”. While the mean score of the students’ writing ability after using Running Dictation Method was 82,75, it was categorized “Excellent”. The result of ttest was 13,57 and ttablewas 2.03 it means that there is a significant Writing ability at the eleventh grade students of SMA Negeri 6 Padangsidimpuan.